2016
DOI: 10.1186/s12967-016-0934-5
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory blood flow during cardiac arrest and cardiopulmonary resuscitation does not correlate with global hemodynamics: an experimental study

Abstract: BackgroundCurrent research highlights the role of microcirculatory disorders in post-cardiac arrest patients. Affected microcirculation shows not only dissociation from systemic hemodynamics but also strong connection to outcome of these patients. However, only few studies evaluated microcirculation directly during cardiac arrest (CA) and cardiopulmonary resuscitation (CPR). The aim of our experimental study in a porcine model was to describe sublingual microcirculatory changes during CA and CPR using recent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In acute models of hemorrhagic shock, tamponade, cardiogenic shock and cardiac arrest coherence exists during the development of shock. In other words, during the development of shock, as signaled by the changes in macrocirculatory parameters, also the microcirculation shows abnormal perfusion parameters [19][20][21][22][23][24][25][26][27]. Although during the development of septic shock, characterized by hypotension and decreased cardiac output (CO), hemodynamic coherence is present [20, [28][29][30].…”
Section: Coherence During the Development Of Circulatory Failurementioning
confidence: 99%
See 1 more Smart Citation
“…In acute models of hemorrhagic shock, tamponade, cardiogenic shock and cardiac arrest coherence exists during the development of shock. In other words, during the development of shock, as signaled by the changes in macrocirculatory parameters, also the microcirculation shows abnormal perfusion parameters [19][20][21][22][23][24][25][26][27]. Although during the development of septic shock, characterized by hypotension and decreased cardiac output (CO), hemodynamic coherence is present [20, [28][29][30].…”
Section: Coherence During the Development Of Circulatory Failurementioning
confidence: 99%
“…As argued earlier, the absence of coherence in this phase may have significant effects on the adequacy of resuscitation as it may result in both over-resuscitation and under-resuscitation. It is clear from experimental models in many different pathophysiologic conditions, including sepsis, that resuscitation on global hemodynamic parameters frequently fails to restore microcirculatory perfusion and oxygenation [25,28,[45][46][47]. The effects in different microcirculatory systems or even within one microcirculatory system may however not be similar [30,48].…”
Section: Coherence In the Treatment Phase: Experimental Datamentioning
confidence: 99%
“…Several animal models have already indicated that such preconditioning is also possible in interventions involving the pancreas, and has a protective effect against postoperative complications . Even if CPR is adequately administered or is uninterrupted, the macro‐ and microcirculation produced does not reach physiological baseline levels and the patient will undergo a relative ischemia or insufficient blood supply . We therefore propose that CPR itself could be a potential trigger for ischemic tissue preconditioning, which could confer subsequent protection from RI and from further ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…We used a similar anesthesia protocol, animal preparation and study outline, including data acquisition methods, as described in our previous study. 7 Briefly, the study was performed on 24 domestic pigs (16 – 20 weeks, weighing 50±3 kg). Anesthesia was initiated by a propofol bolus (2 mg/kg) and continued by the intravenous infusion of propofol (6-8 mg/kg/h), midazolam (0.1 - 0.2 mg/kg/h) and morphine (0.1 - 0.2 mg/kg/h).…”
Section: Methodsmentioning
confidence: 99%